Pricing behavior of the retail gasoline market of Singapore : rockets versus feathers - Chan, Hui Shan (2014)
An inquiry by the Competition Commission of Singapore (CCS) reveals that there is no rocket-and-feather phenomenon in the retail gasoline market of Singapore. This study aims to find out whether there is price asymmetry in the form rocket-and-feather asymmetry in the gasoline market of Singapore. This study uses daily data of retail gasoline and crude oil price between the periods of 01 June 2011 to 19 February 2014. An asymmetric Error Correction Model (ECM) is first estimated and hypotheses of price asymmetry are tested using the Wald tests. Finally the cumulative adjustment function is employed to analyse the short-run adjustment path of retail gasoline price. The results showed that when oil price decreased by 1%, gasoline price decreased by 0.24% after 10 weeks. Conversely, when oil price increased by 1%, gasoline price increased by 0.30%, indicating the presence of the rocket-and-feather phenomenon. The findings from this study are important as it means that CCS has to step in to intervene as well as promote greater price transparency in the gasoline market.